Analisis Determinan Financial Distress pada Bank Umum Syariah di Indonesia : Pendekatan Regresi Logistik Biner dengan Data Panel 2016-2024 - Imro Atul Luthfiyah; Budi Sukardi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this research is to analyze the effect of financial ratios on financial distress in Islamic Commercial Banks in Indonesia. This study uses determinants financial distress that isDebt Ratio (DR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), Return On Equity (ROE), and Operating Expenses Operating Income (BOPO). The population of this study is all Islamic Commercial Banks in Indonesia. The sample taken is the quarterly financial reports of Islamic commercial banks for 9 periods, namely the 2016-2024 period using the purposive sampling and using panel data binary logistic regression testing techniques. Based on the research conducted, the results show that Debt Ratio (DR), Non Performing Financing (NPF), Return On Equity (ROE), and Operational Expenses Operating Income (BOPO) have an effect on financial distress. Whereas Financing to Deposit Ratio (FDR) has no effect on financial distress.